A Weberian Approach to the Ethos of Science - Bourliaguet, Bruno (Teorie vědy / Theory of Science, 2016)
A Weberian Approach to the Ethos of ScienceAbstract: Robert Merton judged his ethos of science as "a limited introduction to a larger problem" in his seminal article. Despite this caution, the ethos has been interpreted, used and criticized as a self-consistent normative structure. As such, critics consider the ethos of science too rudimentary, obsolete or ideological. To overcome these critics, some supporters of the concept propose to revisit or to reconstruct it. This essay is an attempt to satisfy critics and supporters while respecting Merton's legacy. For that purpose, we consider a Weberian paradigm to expand this "limited introduction".Keywords: ethos of science; Robert King Merton; Max Weber; values; norms; rules; orderWeberovský přístup k étosu vědyAbstrakt: Robert Merton ve svém zásadním článku považoval svoje pojetí étosu vědy za "omezený úvod většího problému". I přes toto varování byl étos interpretován, používán a kritizován jako sama o sobě konzistentní normativní struktur. Jako takový jej kritici považují za příliš rudimentární, zastaralý či ideologický. Aby tyto kritiky překonali, zastánci tohoto konceptu prosazují návrat k němu, nebo jeho rekonstrukci. Tato esej představuje snahu uspokojit kritiky i zastánce, zatímco respektuje Mertonův odkaz. Za tímto účelem promýšlíme weberovské paradigma, aby byl tento "omezený úvod" rozšířen.Klíčová slova: étos vědy; Robert King Merton; Max Weber; hodnoty; normy; pravidla; řád